Postabortion contraceptive use in Bahir Dar, Ethiopia: a cross sectional study - Anteneh Mekuria; Hordofa Gutema; Habtamu Wondiye; Million Abera (BMC, 2019)
Abstract Background Although promoting postabortion family planning is very important and effective strategy to avert unwanted pregnancy, less attention was given to it in Ethiopia. Thus, this study aimed to assess contraceptive use and factors which are affecting it among women after abortion in Bahir Dar town. Methods Facility based cross-sectional study was conducted in Bahir Dar town. The data was collected using structured interviewer administered questionnaire from women who obtain the abortion services. Bivariable and multivariable logistic regression was used to evaluate the association that demographic factor and reproductive characteristics have with postabortion contracetive use. Findings with p-value of < 0.05 at 95% CI were considered as statistically significant. Results A total of 400 women who received abortion service were participated in this study. The proportion of postabortion contraceptive use is 78.5%. Single women are 7.2 times more likely use contraceptive after abortion as compared to their counterpart. Contraceptive use is 2 times higher among women who have previous history of abortion as compared to their counterpart. Women who used contraceptive previously and who used contraception for index pregnancy are 4.73 and 2.64 times more likely to use contraceptive after abortion as compared to their counterpart respectively. Conclusion Postabortion contraceptive use is associated with age, marital status, having previous history of abortion, previous contraceptive use and using contraception for index pregnancy. Greater emphasis should be given on providing postabortion contraceptive counselling to increase utilization of postabortion contraceptive use.